Factors affecting community pharmacist’s service for women with chronic diseases during pregnancy and breastfeeding: application of the Health Belief Model - Septi Anggraini, - (Walter de Gruyter, 2019)
Background Pharmacists are known as health care professionals who are responsible for the safety and efficacy of medicine to achieve optimal therapeutic results. Community pharmacists have an opportunity to provide direct services including giving an active medication information service in women during pregnancy and breastfeeding. This study aimed to determine the factors associated with the practice of community pharmacists for actively giving the drug information service for women with chronic diseases during pregnancy and breastfeeding based on the Health Belief Model.